Error Analysis of Determiners in English Students' Final Project Reports: A Comparative Study - Aisyah Khansa, Sarah Syifa; Yessy Purnamasari (Jurusan Bahasa Inggris - Politeknik Negeri Bandung, 2024)
This final project examines an error in the use of determiners identified in the student's final project report. The analysis is based on data from 20 previous final project reports published between 2018 and 2023. A descriptive-qualitative method was used for this project. The data related to sentences were identified using the Dulay taxonomy technique and categorized based on determiners. The study revealed that students in 2018 made more errors compared to students in 2023. The most common incorrect usage of determiners was in the form of articles (84 data), followed by quantifiers (3 data), demonstratives (1 data), and possessives (1 data). According to the findings, students struggled the most with the usage of articles in English writing. They did not seem to have any difficulty using demonstratives, possessives, or quantifiers. The error in the use of determiners resulted in modifications to the determiners. There are five forms of modifications to determiners: addition, omission, misordering, and misformation. The majority of errors were omissions, totaling 58, all of which were in the form of articles, followed by addition (22 errors) and misformation (8 errors). The findings indicate that the majority of students tend to omit articles from their writing.